Nem tudo são flores nesse mar de rosas: um olhar sobre o Hospital do Câncer de Uberlândia - Ferreira, Juliene Barbosa (2010)
Organization culture has been studies by distinct knowledge areas, such as Anthropology Sociology, Psychology and even Administration. The interest on this subject increased in the eighties and a lot of studies have been conducted, in order to understand better what organization culture really is and how it can be analyzed. However, few of those studies have been indeed concerned to understand how is the organization, what it does, how its members behave. Most of them are based on functionalist approach of an integrative and manageable culture, and they analyze only the artifacts. Nevertheless, one understand that culture studies are not are not directed only in that direction, but there are different ways to analyze organization culture, such as Interpretative Anthropology, which considers culture as an interlocking signs system. Ethnographic method consists on the survey of all possible data about a particular community, in order to know better its lifestyle or its specific culture. Sothat, besides using Interpretative Anthropology to build this search, one considered the ideas from Martin (1992, 2002). This author points that culture analysis must involve what is shared by the organization (integrator); what is manifested in groups (differentiator) and also the specific manifestations (fragmented). Based on this approach, this study aims to analyze shared, different and fragmented culture manifestations in the Hospital and show cultural regional traces that influence these manifestations. This was done as a case study in Uberlandia Cancer Hospital, using ethnography and semi-structured interview for data collection. These cultural manifestations raised the analysis categories: a) searching an identity as a Cancer Hospital; b) Concerning to patient health, integrity and well being; c) altruism; d) Power relationship; and e) Rules and Norms accomplishment. The first three categories were associated to integration approach, because they overpass any group formation and are common to any organization. The two are further differentiating and fragmented in some cases. Power relationship shows cultural expressions in specific groups, so they are differentiating. On the other hand there was fragmented manifestation considering power relation as bullying. The category Rules and Norms accomplishment is differentiated, because each employer group behaves in a different way within the organization. Each category is related to national and regional cultural traces, such as hospitality, religion devotion, habit of serving food, elitism, the Brazilian jeitinho and the valorization of relationship. This confirms our position that there are expressions of integration, differentiation and fragmentation which are directly related to cultural traces in HCa.